AGROBISNIS SEKTOR PETERNAKAN AYAM BROILER - -, Astuti (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
Problemsof educated (university graduates)unemployedpeopleshould besolved1;-:eirel-wastemanpowers.Aneffort toreformthegraduates,therefore theycanhelpr:=selvesby creatingtheir own jobs was conducted. The universitygavesome expertise--;:::-rentrepreneurattitudes and skills through aprogramcalles "Magang:r.:ti:ausahaan(MKU)"-rr Suchaprogrampresentedin Biology Departement,FMIPALINY, wasan in-ice trainingonbusinessof boiler raising. Theparticipantswereten selected studens::SemesterVIILSelection wasbasedontheirinterest inrunning businessof broiler::,ising.Theselectedstudentswere thengivensomeknowledgein business management,::oposing newbusiness,composingchickendiet,and techniquesin raisingbroiler.Theibilorvingstep was thensending thestudents tothe link industry.The linkindustrylocated inWonosalam,Ngemplak, Sleman.During thetrainingst';dentsworkedanykindclf scheduled jobs shiftinglyunder supervisionofbusinesso\\ner. Thelecturerteam visitedregularlyonceaweek. It was expectedthatallstudentscoulddoanykindof job relatedto raising broiler.and theentrepreneurattitudescouldder,elopdue totheir involvementinbusiness.Itwasagood pointfor the students thatthebusinessownerwas very supportiveto thisand the followingprogram.Inordertoevaluatestudentsunderstanding andinvolvementin thebusiness,theywererequiredtopresentabusinessproposalinbroiler raising. Onthe basis of the successofthisprogram,Departementof BiologyIiMIPALINY encouragestodevelopprogramsof laboratorypracticeand field workwhichhave entreprenuerperspectivein order tointegratetheentrepreneurshipto theexisted curruculum